2017
DOI: 10.1007/s10735-017-9737-0
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of LGR4 inhibits proliferation and odonto/osteogenic differentiation of stem cells from apical papillae

Abstract: During tooth root development, stem cells from apical papillae (SCAPs) are indispensable, and their abilities of proliferation, migration and odontoblast differentiation are linked to root formation. Leucine-rich repeat-containing GPCR 4 (LGR4) modulates the biological processes of proliferation and differentiation in multiple stem cells. In this study, we showed that LGR4 is expressed in all odontoblast cell lineage cells and Hertwig's epithelial root sheath (HERS) during the mouse root formation in vivo. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…It has been reported that LGR4, 5, and 6 are strong potentiators of Wnt/β‐catenin signaling . Several studies have highlighted the crucial role of LGR4 in the promotion of osteoblast differentiation by activating the Wnt signaling pathway . Intriguingly, in the present study, BMP9 had no effect on the expression level of the LGR4 gene but dramatically augmented the expression of the LGR6 gene.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that LGR4, 5, and 6 are strong potentiators of Wnt/β‐catenin signaling . Several studies have highlighted the crucial role of LGR4 in the promotion of osteoblast differentiation by activating the Wnt signaling pathway . Intriguingly, in the present study, BMP9 had no effect on the expression level of the LGR4 gene but dramatically augmented the expression of the LGR6 gene.…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the mesenchymal compartment, the complementary expression patterns of RANK and LGR4 in the dental pulp and dental follicle (observed at day 5 in the first molar) suggest the existence of a differential impact of RANKL on mesenchymal cells in both these sites with a probable histogenesis function. Interestingly, the expression pattern of LGR4, in the complex formed by the tooth, periodontium and alveolar bone, appeared to change sequentially from the initial morphogenesis stage [24] to the dental eruption stage [25,26], suggesting a dynamic/evolutive function of this receptor for RANKL and R-spondin2 throughout dental development, the modalities of which remain to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…Cell cycle arrest is an important mechanism to inhibit cell proliferation. Many factors inhibit cell proliferation by modulating cell cycle progression . It is well known that the core of the cell cycle regulation mechanism is a group of cell cycle dependent protein kinase (CDKs), which is dependent on their regulatory subunit cyclins.…”
Section: Discussionmentioning
confidence: 99%